Generation of an equine biobank to be used for Functional Annotation of Animal Genomes project. (11th October 2018) - Burns, E. N.; Bordbari, M. H.; Mienaltowski, M. J.; Affolter, V. K.; Barro, M. V.; Gianino, F.; Gianino, G.; Giulotto, E.; Kalbfleisch, T. S.; Katzman, S. A.; Lassaline, M.; Leeb, T.; et al.
Summary: The Functional Annotation of Animal Genomes (FAANG) project aims to identify genomic regulatory elements in both sexes across multiple stages of development in domesticated animals. This study represents the first stage of the FAANG project for the horse, Equus caballus . A biobank of 80 tissue samples, two cell lines and six body fluids was created from two adult Thoroughbred mares. Ante‐mortem assessments included full physical examinations, lameness, ophthalmologic and neurologic evaluations. Complete blood counts and serum biochemistries were also performed. At necropsy, in addition to tissue samples, aliquots of serum, ethylenediaminetetraacetic acid (EDTA) plasma, heparinized plasma, cerebrospinal fluid, synovial fluid, urine and microbiome samples from all regions of the gastrointestinal and urogenital tracts were collected. Epidermal keratinocytes and dermal fibroblasts were cultured from skin samples. All tissues were grossly and histologically evaluated by a board‐certified veterinary pathologist. The results of the clinical and pathological evaluations identified subclinical eosinophilic and lymphocytic infiltration throughout the length of the gastrointestinal tract as well as a mild clinical lameness in both animals. Each sample was cryo‐preserved in multiple ways, and nuclei were extracted from selected tissues. These samples represent the first published systemically healthy equine‐specific biobank with extensive clinical phenotyping ante ‐ and post‐mortem . The tissues in the biobank are intended for community‐wide use in the functional annotation of the equine genome. The use of the biobank will improve the quality of the reference annotation and allow all equine researchers to elucidate unknown genomic and epigenomic causes of disease.